Effect of Organic Solvents on the Inclusion of Sparfloxacin and Norfloxacin with b-Cyclodextrin - A.F. Al-Rawashdeh, Nathir (Asian Journal of Chemistry, 2012)
The complexation of sparfloxacin (SPR) and norfloxacin (NOR) by <span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-cyclodextrin (<span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-CD) in water and in mixed organic/aqueous media has been studied by absorption spectroscopy. Three organic solvents [dimethyl-sulphoxide, ethanol and 2-methyl-1-propanol have been adopted which differ in polarity and hydrophobicity. It has been shown that the presence of organic solvent causes the degradation of the 1 : 1 SPR : <span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-CD and NOR : <span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-CD complexes. The binding constants of the inclusion complexes of SPR and NOR with <span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-CD in water are greater than those with mixed organic-water media. The higher the hydrophobicity of the co-solvent, the weaker the complexation of SPR and NOR by <span style="line-height: 115%; font-family: Symbol; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">b-CD.